Synthesis and study of mixed ligand-metal complexes of 1, 3, 7-trimethylxanthine and 1, 3-dimethyl-7H-purine-2, 6-dione with some other ligands - Shaker S.A. (Hindawi Limited, 2023)
This work presents synthesis and study of a new mixed ligand metal complexes of 1,3,7-trimethylxanthine and 1,3-dimethyl-7H-purine-2,6-dione with some other ligands like SCN and OCN ions to give the general formula [M(Tx) 2(Tp)2XY] where M=Co(II), Ni(II), Cu(II), Zn(II) and Cd(II), Tx=1,3,7-trimethylxanthine, Tp= 1,3-dimethyl-7H-purine-2,6-dione, X= SCN and Y=OCN. The resulting products were found to be solid which have been characterized using UV-Visible and infrared spectroscopy. Elemental analyses were performed using C, H, N analysis and atomic absorption techniques. The magnetic susceptibility and the conductivity were also measured. The present results suggest that the 1,3,7-trimethylxanthine and 1,3-dimethyl-7H-purine-2,6- dione were coordinated with metal ions through the nitrogen atom. Thiocyanate ion was coordinated with metal ions through the sulfur atom and the cyanate ion was coordinated with metal ions through the oxygen atom.